COMPARATIVE LEGISLATIVE ANALYSIS OF ACTIVE BRIBERY IN THE UNITED KINGDOM OF GREAT BRITAIN AND NORTHERN IRELAND - Mijo Galiot (Zbornik Pravnog Fakulteta Sveučilišta u Rijeci, 2015)
Confronting socially unacceptable activities, especially corruptive criminal acts, including bribing, makes an important issue of every regulated legal system. The crucial part of such policies are the criminal polices. In this paper, the author deals with the criminal legislation of the United Kingdom of Great Britain and Northern Ireland, related to the matters of active bribing as one of the basic forms of corruptive behaviour. While comparing the way the penal system is regulated in the said country, the author comments basic similarities and differences of the passive bribing legal regulation in the United Kingdom and the Republic of Croatia.